Development and psychometric validity of the perioperative anxiety scale-7 (PAS-7) - Chengjiao Zhang; Xitong Liu; Tianran Hu; Fei Zhang; Lingyi Pan; Yan Luo; Zhen Wang (BMC Psychiatry, 2021)
Abstract Background Preoperative anxiety is a common psychological reaction in perioperative patients. The absence of a valid measurement tool hinders the evaluation of interventions to treat preoperative anxiety in China. This study aims to develop the Perioperative Anxiety Scale-7 (PAS-7) and test its reliability, validity, and cut-off value. Methods A total of 280 patients over 16 years old (M = 55.1, SD = 14.3) who were undergoing elective surgery were recruited to complete the PAS-7 and the Generalized Anxiety Disorder-7 scale (GAD-7) one day before surgery. Results The PAS-7 included seven items divided into two dimensions: mental anxiety and somatic anxiety. These two dimensions could explain 74.294% of the population variance. The internal consistency of each dimension ranged from 0.761–0.933. The confirmatory factor analysis showed that the model fit of the scale was good (χ 2 = 34.798, df = 13, χ 2 /df = 2.677, CFI = 0.949, TLI = 0.918, SRMR = 0.057, RMSEA = 0.115). The correlations between the GAD-7 and each dimension and the scale’s total score were significant (0.711–0.789). A cut-off score of 8, maximizing the Youden Index, yielded a sensitivity of 75% and a specificity of 84.6% (95% CI: 0.88 ~ 0.97). Conclusions The PAS-7 had good reliability and validity and could be used as an effective tool to evaluate preoperative anxiety.